Antitrust analysis of platform markets why the Supreme Court got it right in American Express - Evans, David S. 1954-; Schmalensee, Richard 1944- (Competition Policy International, 2019)
This book compiles a set of pieces on the implications of the U.S. Supreme Court's ruling in Ohio et. al. v. American Express and the preceding litigation for the treatment of multisided platforms under U.S. antitrust law. The authors consider that the Supreme Court ruling provides valuable guidance for antitrust analysis in such markets
Keywords: Antitrustrecht; Marktregelung; Internationales Kartell; USA